2001
DOI: 10.1183/09031936.01.17509340
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled nitric oxide in chronic obstructive pulmonary disease: relationship to pulmonary function

Abstract: The following study was undertaken in order to determine how exhaled nitric oxide (eNO) levels in former smokers with chronic obstructive pulmonary disease (COPD) compared to eNO levels in patients with asthma and in healthy nonsmoking volunteers. The study also aimed to determine any relationship between eNO levels in COPD and: 1) conventional measures of lung function; and 2) inhaled corticosteroid (ICS) use.In former smokers with COPD, nonsmokers with asthma and volunteers, eNO levels, spirometry, lung volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 13 publications
2
52
0
1
Order By: Relevance
“…Moreover, lung function parameters such as FEV 1 and DL CO were inversely correlated with exhaled NO levels [14]. This increased flux of NO from the airways was significantly decreased after inhalation of aminoguanidine, a relatively selective iNOS inhibitor [25].…”
Section: Asthmamentioning
confidence: 81%
See 3 more Smart Citations
“…Moreover, lung function parameters such as FEV 1 and DL CO were inversely correlated with exhaled NO levels [14]. This increased flux of NO from the airways was significantly decreased after inhalation of aminoguanidine, a relatively selective iNOS inhibitor [25].…”
Section: Asthmamentioning
confidence: 81%
“…Lung function parameters such as forced expiratory volume in 1 s (FEV 1 ) and carbon monoxide diffusing capacity (DL CO ) were inversely correlated with eNO levels in patients with COPD. In contrast to patients with asthma, the use of inhaled corticosteroids had no significant influence on eNO levels in patients with COPD [14]. Brindicci et al measured eNO at multiple expired flows to make a distinction between alveolar and bronchial NO and found that COPD is associated with elevated alveolar NO [15].…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…However, because other markers of early detection have only been used in recipients of SSLTx/HLTx [7,8] or are difficult to interpret in SLTx recipients (for instance, the FEF25-75%), it still had to be confirmed that eNO values do not depend upon the nature of the transplantation procedure and, hence, that the native lung after SLTx has no major impact on the measurement of eNO. This is of particular interest, since it has previously been demonstrated that the eNO value in COPD patients is increased [17] and that eNO values correlate negatively with FEV1, with the lower FEV1 values corresponding to higher eNO values [18]. Moreover, an association has been found between eNO values and bronchial inflammation in COPD patients, as assessed by using induced sputum neutrophilia and interleukin-8 [19].…”
Section: Discussionmentioning
confidence: 98%